The transformative role of technology in corporate governance: A conceptual and practical perspective - Lima, Demir; Nimani, Artan; Spahija, Denis (Edelweiss Applied Science and Technology, 2025)
In recent decades, technological transformation has profoundly affected the way organizations structure, lead, and oversee their strategic functions. Corporate governance, as a fundamental mechanism for maintaining a balance between the interests of shareholders, management, and other stakeholders, is undergoing a profound change as a result of technological developments. Digital technologies, including real-time communication platforms, automated reporting systems, advanced analytics, and artificial intelligence, are reshaping the way companies make strategic decisions, increasing transparency and strengthening accountability mechanisms. This paper aims to systematically analyze the strategic role of technology in the development and consolidation of corporate governance, emphasizing its impact on board structures, decision-making processes, transparency, and internal control. Through a theoretical and analytical approach, the paper reviews relevant literature and contemporary models of corporate governance in the context of digital transformation. It also addresses the challenges encountered in implementing technology in corporate environments, such as cybersecurity, data protection, legal regulation, and the lack of digital skills at leadership levels. The expected results of the study highlight that technology is not just an auxiliary instrument but a strategic factor that can strengthen corporate governance mechanisms, increase trust between stakeholders, and contribute to the sustainable growth of organizations. The paper concludes with practical recommendations for the more effective integration of digital technologies into corporate governance structures, based on international best practices.